Left main bronchial sleeve resection with total lung parenchymal preservation: a tailored surgical approach. (12th November 2019) - Mantovani, Sara; Gust, Lucile; D'Journo, Xavier Benoit; Thomas, Pascal Alexandre
Abstract: Bronchial sleeve resection is an uncommon thoracic surgical procedure. Under specific conditions, patients can be selected to undergo a sleeve resection of the main bronchus with complete parenchymal preservation. The left main bronchus is longer than the contralateral bronchus, therefore left endobronchial tumours can be localized at the proximal end of the bronchus or distally, near the secondary carina. Bronchial anastomosis in these 2 situations requires different approaches. We present the surgical technique of left main bronchus resection with complete preservation of lung parenchyma through a hemi-clamshell incision (proximal tumour) or posterolateral thoracotomy (distal tumour).